If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3y + 5) = 3(5y + 0.66) Reorder the terms: 2(5 + 3y) = 3(5y + 0.66) (5 * 2 + 3y * 2) = 3(5y + 0.66) (10 + 6y) = 3(5y + 0.66) Reorder the terms: 10 + 6y = 3(0.66 + 5y) 10 + 6y = (0.66 * 3 + 5y * 3) 10 + 6y = (1.98 + 15y) Solving 10 + 6y = 1.98 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. 10 + 6y + -15y = 1.98 + 15y + -15y Combine like terms: 6y + -15y = -9y 10 + -9y = 1.98 + 15y + -15y Combine like terms: 15y + -15y = 0 10 + -9y = 1.98 + 0 10 + -9y = 1.98 Add '-10' to each side of the equation. 10 + -10 + -9y = 1.98 + -10 Combine like terms: 10 + -10 = 0 0 + -9y = 1.98 + -10 -9y = 1.98 + -10 Combine like terms: 1.98 + -10 = -8.02 -9y = -8.02 Divide each side by '-9'. y = 0.8911111111 Simplifying y = 0.8911111111
| 2x^3-5x+20=0 | | 6(7-x)+x=36+u | | 22=n | | 4-7(1-5x)=25 | | 3(8-5x)=-2x-4 | | 17=3(7y-8) | | 2y-66=y-16 | | 0.5x=x-200000 | | I-92=-90 | | x+(20+2)=85 | | -17+x=-22 | | -44+o=24 | | -12a=-12 | | 4u+36=7u+6 | | 19+R=27 | | -11+x=-18 | | u-40=2u-98 | | 3+H=19 | | N-65=-53 | | G-19=11 | | 3sin*2x-6cos^2x=0 | | x+(x+12)=150 | | R+40=75 | | -240x^2=24000 | | 13b=-39 | | 2(x-3)2-40=0 | | 9a(a+1)= | | (5x-3)-2(2x-3)=3(x-1)+2(4x-7) | | 3(5x+8)=13 | | 11/2c=6 | | x+(x+6)=58 | | -25y+-55= |